FEASTING THROUGH TIME: A LITERATURE SURVEY OF SOUTH INDIAN TRIBAL FOOD HABITS (International Journal of Food and Nutritional Sciences, 2022)
This paper provides a comprehensive examination of the food habits of various South Indian tribes, integrating historical perspectives with ethnobotanical insights. It highlights the influence of geography, cultural practices, and ecological factors on tribal diets, drawing from existing literature. By analyzing the culinary traditions of specific tribes, this survey aims to enrich our understanding of the region's diverse food systems.